Effects of physical exercise on college students’ academic self-efficacy: the chain mediating role of future orientation and mental toughness - Jiang, Yong; Fu, Yifeng; Dong, Xinqiu (Frontiers in Psychology, 2025)
IntroductionAcademic self-efficacy affects students’ behavioral styles, efforts, and attitudes toward academic difficulties in the learning process. Physical education, as a core vehicle of education, and physical exercise, as an important way to promote physical and mental health, have special value for the development of academic self-efficacy. The study explored the effects of physical exercise on college students’ academic self-efficacy and the chain-mediated effects of future orientation and mental toughness.MethodsA total of 624 college students were surveyed using the physical exercise Rating Scale, Academic Self-Efficacy Scale, Future Orientation Scale, and Mental Toughness Scale, and the mediating role of Future Orientation and Mental Toughness was examined and analyzed by using Structural Equation Modeling and Bootstrap Method.Results① physical exercise and academic self-efficacy were positively correlated, and the direct prediction of academic self-efficacy was significant; ② physical exercise can positively predict future orientation, future orientation can positively predict mental toughness and academic self-efficacy, and mental toughness can positively predict academic self-efficacy; ③ future orientation and mental toughness play a significant mediating role in the relationship between physical exercise and academic self-efficacy. The three pathways of mediating effects: physical exercise and academic self-efficacy, and mental toughness. Three pathways of mediating effects were found: physical exercise→future orientation→academic self-efficacy (Path 1), physical exercise→mental toughness→academic self-efficacy (Path 2), and physical exercise→future orientation→mental toughness→academic self-efficacy (Path 3).